Strategic Management of Islamic Education: Revealing The Challenges of Professionalism - Sakarina, Sari; Pratiwi, Ratih; Surahman, Susilo; Cakranegara, Pandu Adi; Arifin, Arifin (JURNAL AL-TANZIM, 2022)
This study aims to identify and analyze the application of strategic management in revealing the challenges of professionalism in the Digitalization Era. This study used a qualitative method with a case study design. Data were collected through interviews, observations, and documentation. The data were tested for validity and analyzed by data reduction, presentation, and conclusion. This study showed that the strategic management of Islamic education in revealing the challenges of professionalism in the Digitalization Era at Madrasah Ibtidaiyah Negeri 1 Sambas changed in terms of the culture of the teaching and learning process and teacher performance based on intense digitalization. In terms of management, the principal at MIN 1 Sambas has implemented a Madrasa-Based Management Strategy in the Digital Era and carried out Online Training Program for the teachers.